Fracture Resistance of Endodontically Treated Maxillary Premolars Restored by Various Direct Filling Materials: An In Vitro Study - Mincik, Jozef; Urban, Daniel; Timkova, Silvia; Urban, Renata (International Journal of Biomaterials, 2016)
The aim of this study is to compare the effect of various restorative materials on fracture resistance in maxillary premolars. Premolars (n=64) with no restorations or cracks were selected. MOD cavities were prepared considering the buccolingual width to be equal to half of the intercuspal distance. The specimens were randomly divided into 8 groups, 8 specimens each: group A intact teeth, group B unfilled cavity, group C composite made by oblique layering technique, group D composite with 2 mm cusp coverage, group E bulk-filled posterior composite, group F glass-ionomer, group G amalgam, and group H composite with proximal boxes. The specimens were subjected to an axial compression load with the mean values of fracture resistance in group A: 1289 N, group B: 181.75 N, group C: 445.38 N, group D: 645.88 N, group E: 355.13 N, group F: 352.00 N, group G: 191.38 N, and group H: 572.00 N. There was no significant difference between groups B and G, between C and D, E, and F, and between group D and H. All other measurements were statistically significant. We conclude that composite restoration with cusp coverage is the most ideal nonprosthetic solution for endodontically treated teeth. Cusp coverage increases the fracture resistance compared to the conventional cavity design.